Facile synthesis of cerium doped Co-Mn-FeO nano ferrites as highly sensitive and fast response humidity sensors at room temperature - S.A. Al-Ghamdi (Journal of King Saud University: Science)
Herein, this work presents the facile synthesis of Cerium (Ce3+) doped Cobalt-manganese-iron oxide ferrite as an effective humidity sensor operated at ambient temperature. This work reports, one step solution combustion technique to synthesize Co0.5Mn0.5Fe2−xCexO4 (x = 0.0, 0.050 and 0.1) ferrites. The structural and morphological features of the synthesized Co0.5Mn0.5Fe2−xCexO4 ferrites NPs were investigated through scanning electron microscope (SEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and ultraviolet visible (UV–visible) spectroscopy. The XRD results indicates the creation of single phase in pure Co0.5Mn0.5Fe2−xCexO4 ferrite that remains unchanged by the mechanism of Ce3+inclusion. The humidity sensing mechanism was systematically investigated using adsorption–desorption isotherms. Highest humidity sensing response was achieved for Co0.5Mn0.5Fe2−xCexO4 (x = 0.1) ferrite of the order of 98 % in comparison to the pure Co0.5Mn0.5Fe2−xCexO4 (x = 0) which is about 41 %. The sensors response and recovery times for the Co0.5Mn0.5Fe2−xCexO4 (x = 0.1) was recorded to be 36 s and 63 s respectively and the sensors long term stability was examined for a duration of 90 days. The results of the present investigation offer new dimensions to fabricate high performance, room temperature operable humidity sensors for next generation sensors applications.